Application of electrohydraulic effect for stripping from terminals of plastic parts - V. F. Kovalevskiy; S. B. Skobelev; G. G. Bury (Омский научный вестник)
The paper reviews the methods for cleaning plastic parts. The physics of the electrohydraulic effect processor L. A. Yutkin is considered. The design of the pilot plant, as well as the interchangeable devices used to remove the flare from the terminals of the plastic parts, is presented. The results of experimental studies of the application of the electrohydraulic effect for the removal of a cover are presented. During the processing, the thick layer of stripping is completely removed from the leads in 1–2 minutes. On the conclusions of the details there are small areas covered with a layer of a few micrometers thick.